Pembuatan Game Edukasi Tebak Gambar Berbasis Andoid - Dewantara Dewantara; Khairil Khairil; Achmad Fikri Sallaby (UNIVED Press, 2025)
The current development of technology provides great opportunities in the field of education, one of which is through educational game media. This research aims to design and develop an Android-based educational game that can be used as an interactive learning medium for early childhood, specifically for students of Pajar Harapan Kindergarten in South Bengkulu Regency. This game features a picture guessing concept with three main themes: names of animals, names of fruits, and Indonesian national heroes, where players must arrange letters or answer multiple-choice questions based on the images displayed. The development method used is the Waterfall model, which includes stages of analysis, design, implementation, testing, and maintenance. Testing results indicate that this game can enhance children's interest in learning by presenting material in a fun and interactive manner. Feedback from teachers and students regarding this application is also positive, indicating that the game is effective as an alternative learning medium. It is hoped that this application can continue to be developed and used more widely in early childhood education environments